2009
DOI: 10.1017/s0022226708005550
|View full text |Cite
|
Sign up to set email alerts
|

Phrase structure vs. dependency: The analysis of Welsh syntactic soft mutation

Abstract: Most familiar syntactic frameworks recognize the category ‘phrase’, and are built around phrase structure relationships. However, the Word Grammar dependency model does not acknowledge the category ‘phrase’ as a primitive in the grammar; instead, all relationships are word-based, with phrases having no syntactic status. Here, I investigate the theoretical validity of the notion ‘phrase’ by examining the phenomenon in Welsh known as syntactic soft mutation, contrasting a phrase-based account with a dependency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mutation has been analyzed extensively in the lin-guistic literature, e.g. Awbery (1973), Lieber (1983), Tallerman (1990), Kibre (1997), Pyatt (1997), Green (2006), Mittendorf & Sadler (2006), Wolf (2007), Stammers (2009), Tallerman (2009), Iosad (2010, Hammond (2011), Hannahs (2011), Hannahs (2013, Prys (2015), etc. The facts of this section are consistent with standard descriptive and pedagogical sources on Welsh, e.g.…”
Section: Mutation In Welshmentioning
confidence: 99%
“…Mutation has been analyzed extensively in the lin-guistic literature, e.g. Awbery (1973), Lieber (1983), Tallerman (1990), Kibre (1997), Pyatt (1997), Green (2006), Mittendorf & Sadler (2006), Wolf (2007), Stammers (2009), Tallerman (2009), Iosad (2010, Hammond (2011), Hannahs (2011), Hannahs (2013, Prys (2015), etc. The facts of this section are consistent with standard descriptive and pedagogical sources on Welsh, e.g.…”
Section: Mutation In Welshmentioning
confidence: 99%
“…The German grammar is carried out in parsing method. According to Tallerman (2009), for the recognition of phrase structure and its category, the syntactic framework is used.…”
Section: Phrase Structurementioning
confidence: 99%
“…Supporters of phrase structure will no doubt argue that the long history of research in phrase structure has shown a great many other properties of sentence structure that follow from configurations in phrase structure. The trouble with these arguments is that phrase structure is virtually always taken for granted, and alternative analyses in terms of dependency structure are rarely considered (though there are exceptions: Tallerman, 2009). One of the most productive areas of syntactic research has been the detailed analysis of extraction, where phrase structure has played a prominent part; but here too dependency structure provides a satisfactory basis for analysis, provided we allow sufficiently rich structures.…”
mentioning
confidence: 99%